Anger and positive emotions in political protest (2014)
This study analyses the role played by emotions in protest. In the current explanatory models, anger is the sole emotion associated with these actions. But is anger the only motive capable of mobilising citizens to defend a cause? We believe not. Hence, we postulate that anger, along with other emotions of positive valence, must act jointly to facilitate protest. To test this hypothesis, a questionnaire was applied to 316 university students in a setting of cut-backs in education. The results highlight several interesting aspects. Firstly, anger correlated significantly and positively with the positive emotions. Secondly, the mediation analysis performed showed: a) the relevance of positive emotions for explaining the intention to participate; and b) the influence of anger on the intention to participate is fundamentally through positive emotions. We will also discuss the role of emotions and the need to extend the motives involved in political actions.